2001
DOI: 10.1159/000052812
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fallers in a Community-Based Sample of People with Parkinson’s Disease

Abstract: Background: The risk of people with Parkinson’s disease (PD) falling is greater than that of the general population but to date, disease-specific predictors of falling have not been identified. Objectives: To identify one or more features, which would predict individuals at risk of falling during a 3-month prospective follow-up study. Method: A battery of standardised tests administered in the home and the laboratory with a 3-month follow-up telephone interview. Results: Sixty-three people with PD were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 24 publications
(23 reference statements)
9
113
2
1
Order By: Relevance
“…These found relative risks (RRs) of 2.4 (95% CI 1.9 to 2.9), 9 2.6 (no CI given), 10 and 2.5 (1.9 to 3.4) 6 and ORs of 3.7 (1.3 to 10.0) 11 and 2.4 (1.3 to 4.4). 12 Among 10 Class II studies, ORs were 3.0 (1.3 to 7.3), 13 16.0 (4.4 to 58.0), 14 5.0 (1.2 to 20.9), 15 2.0 (1.2 to 3.5), 16 3.5 (1.2 to 9.6), 17 2.4 (1.3 to 4.4), 12 5.4 (1.8 to 15.7), 18 3.1 (2.2 to 4.4), 19 12.5 (3.0 to 52.2), 20 and 4.0 (1.3 to 12.1). 21 Other Class II follow-up studies reported RRs of 1.9 (1.3 to 2.9) and 1.8 (1.3 to 2.4), 22 and 2.0 (1.3 to 3.1).…”
Section: Analysis Of Evidence Risk Of Falls Deter-mentioning
confidence: 99%
“…These found relative risks (RRs) of 2.4 (95% CI 1.9 to 2.9), 9 2.6 (no CI given), 10 and 2.5 (1.9 to 3.4) 6 and ORs of 3.7 (1.3 to 10.0) 11 and 2.4 (1.3 to 4.4). 12 Among 10 Class II studies, ORs were 3.0 (1.3 to 7.3), 13 16.0 (4.4 to 58.0), 14 5.0 (1.2 to 20.9), 15 2.0 (1.2 to 3.5), 16 3.5 (1.2 to 9.6), 17 2.4 (1.3 to 4.4), 12 5.4 (1.8 to 15.7), 18 3.1 (2.2 to 4.4), 19 12.5 (3.0 to 52.2), 20 and 4.0 (1.3 to 12.1). 21 Other Class II follow-up studies reported RRs of 1.9 (1.3 to 2.9) and 1.8 (1.3 to 2.4), 22 and 2.0 (1.3 to 3.1).…”
Section: Analysis Of Evidence Risk Of Falls Deter-mentioning
confidence: 99%
“…It has been emphasized that the incidence of falls in PD is high. In the past few years, six prospective studies have examined fall rates and consequently falls among communitydwelling patients with PD living in Canada, Netherlands, Australia and United Kingdom (Ashburn et al, 2001;Bloem et al, 2001;Bloem & Bathia, 2004;Hely et al, 1999;Temlett & Thompson, 2006;Morris, 2000). All these studies included patients suffering from Idiopathic PD who were able to walk and had no other causes for falls.…”
Section: Epidemiology Of Fallsmentioning
confidence: 99%
“…[8][9][10][11][12] Many of these measures have limitations exist including low sensitivity and/or specificity 8,13 ceiling effects 16,15 and inclusion of items that physical therapy intervention cannot address (such as prior number of falls). 11,16,17 Some research has shown that a battery of tests is necessary to fully assess balance, however, a consensus on which tests to include and interpretation of results from multiple tests has not been reached. 9,13,18 To evaluate postural stability in a more functional context, these clinical scales would appear to be more appropriate than simple tests of postural stability.…”
mentioning
confidence: 99%